Effectiveness and safety of nicotine replacement therapy assisted reduction to stop smoking: systematic review and meta-analysis. (2nd April 2009) - Moore, David; Aveyard, Paul; Connock, Martin; Wang, Dechao; Fry-Smith, Anne; Barton, Pelham
Abstract : Objective To determine the effectiveness and safety of nicotine replacement therapy assisted reduction to stop smoking. Design Systematic review of randomised controlled trials. Data sources Cochrane Library, Medline, Embase, CINAHL, PsychINFO, Science Citation Index, registries of ongoing trials, reference lists, the drug company that sponsored most of the trials, and clinical experts. Review methods Eligible studies were published or unpublished randomised controlled trials that enrolled smokers who declared no intention to quit smoking in the short term, and compared nicotine replacement therapy (with or without motivational support) with placebo, no treatment, other pharmacological therapy, or motivational support, and reported quit rates. Two reviewers independently applied eligibility criteria. One reviewer assessed study quality and extracted data and these processes were checked by a second reviewer. The primary outcome, six months sustained abstinence from smoking beginning during treatment, was assessed by individual patient data analysis. Other outcomes were cessation and reduction at end of follow-up, and adverse events. Data synthesis Seven placebo controlled randomised controlled trials were included (four used nicotine replacement therapy gum, two nicotine replacement therapy inhaler, and one free choice of therapy). They were reduction studies that reported smoking cessation as a secondary outcome. The trials enrolled a total of 2767 smokers, gave nicotine replacement therapy for 6-18 months, and lasted 12-26 months. 6.75% of smokers receiving nicotine replacement therapy attained sustained abstinence for six months, twice the rate of those receiving placebo (relative risk (fixed effects) 2.06, 95% confidence interval 1.34 to 3.15; (random effects) 1.99, 1.01 to 3.91; five trials). The number needed to treat was 29. All other cessation and reduction outcomes were significantly more likely in smokers given nicotine replacement therapy than those given placebo. There were no statistically significant differences in adverse events (death, odds ratio 1.00, 95% confidence interval 0.25 to 4.02; serious adverse events, 1.16, 0.79 to 1.50; and discontinuation because of adverse events, 1.25, 0.64 to 2.51) except nausea, which was more common with nicotine replacement therapy (8.7% v 5.3%; odds ratio 1.69, 95% confidence interval 1.21 to 2.36). Conclusions Available trials indicate that nicotine replacement therapy is an effective intervention in achieving sustained smoking abstinence for smokers who have no intention or are unable to attempt an abrupt quit. Most of the evidence, however, comes from trials with regular behavioural support and monitoring and it is unclear whether using nicotine replacement therapy without regular contact would be as effective.